2015
DOI: 10.3109/02770903.2015.1067321
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct phenotypes of asthma in elite athletes identified by latent class analysis

Abstract: Two asthma phenotypes were identified in elite athletes: "atopic asthma" and "sports asthma". The type of sport practiced was associated with different phenotypes: water and winter sport athletes had three- and ninefold increased risk of "sports asthma". Recognizing different phenotypes is clinically relevant as it would lead to distinct targeted treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 28 publications
3
53
2
1
Order By: Relevance
“…Both training in a cold air and swimming pool environment had been previously identified as risk factors for EIBw A and were recently confirmed . Another recent study evidenced that EIB was present in 60% of swimmers and 29% of cold‐weather athletes compared to only 17% of nonathlete controls .…”
Section: Development and Risk Factors For Eib In Athletesmentioning
confidence: 66%
See 1 more Smart Citation
“…Both training in a cold air and swimming pool environment had been previously identified as risk factors for EIBw A and were recently confirmed . Another recent study evidenced that EIB was present in 60% of swimmers and 29% of cold‐weather athletes compared to only 17% of nonathlete controls .…”
Section: Development and Risk Factors For Eib In Athletesmentioning
confidence: 66%
“…Previously, the possibility of two different phenotypes among athletes has been suggested: the pattern of “classical asthma” characterized by early onset of asthma in childhood, bronchial hyper‐responsiveness (BHR) diagnosed by methacholine challenge, atopy and signs of eosinophilic airway inflammation; and another phenotype with onset of respiratory symptoms during sports career, BHR to eucapnic hyperventilation test (EVH) and a variable association with atopic markers and eosinophilic airway inflammation . More recently, using latent class analysis, Couto et al identified two distinct phenotypes of EIB in athletes: “atopic asthma” defined by the occurrence of allergic sensitization, increased levels of exhaled nitric oxide, rhinitis and other allergic comorbidities; and “sports asthma”, defined by the presence of exercise‐induced respiratory symptoms and BHR in the absence of allergic features. Of note, these two phenotypes match with the proposed definitions of EIB A and EIBw A .…”
Section: Introductionmentioning
confidence: 99%
“…Both are endurance sports and thus associated with an increased risk of asthma; however, winter sports athletes may be at a greater risk because of the repeated and prolonged inhalation of cold, dry air. Others have also found that winter sport is a risk factor for the specific phenotype of sports asthma (27).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of asthma and exercise‐induced bronchoconstriction and corresponding treatments within the athletic population has been a topic of considerable debate in the past . It appears established today that distinct phenotypes of asthma exist among elite athletes and that individuals of specific sport disciplines such as water and winter sports are significantly more often affected by exercise‐induced bronchoconstriction . Enabling asthmatic athletes’ to participate in elite sport while ensuring appropriate medical treatment with relevant β 2 ‐agonists is regulated by WADA, with regulations being frequently revisited and scrutinized with regards to effects of (non)permitted drug use on both the athletic performance as well as drug testing.…”
Section: Anabolic Agentsmentioning
confidence: 99%